Hollar “copia” Leonardo: l’uso della carta lucida per incisioni in scala 1:1 - Melani, Margherita (Incontri. Rivista europea di studi italiani, 2020)
Hollar “copied” Leonardo: The use of ‘carta lucida’ for incisions on a 1:1 scale Hollar “copied” Leonardo for Lord Arundel and, as already demonstrated, in some cases he did it in real size (1:1). In this work process Hollar, following a technique already described by Cennino Cennino in his Book of Art, uses carta lucida: a sheet of paper made transparent through the use of oils that allows him to have an exact copy on the real size of any works of art. An example of this working process can be one drawing attributed to the Follower of Leonardo da Vinci now at the Teylers Museum in Haarlem (inv. A 5). It is an ink drawing on carta lucida with the copy in the real size of a man seen in profile, from the left side of a drawing of Leonardo with a couple of men represented en face (Windsor, RL 12490). The size of the male figure reproduced in Leonardo’s autograph, in the Harlem copy as well as in the Hollar’s engraving is always almost identical. A dimensional match that allows to formulate a new proposal for attribution and to include the Haarlem’s drawing in the corpus of Hollar’s drawings as an example of his workflow.